Internal Control in the Economics of Corporations - TATYANA P. Karpova; VICTORIA V. Karpova (Учёт. Анализ. Аудит, 2019)
The creation of corporations, holding companies, interregional industrial and other sectoral groups in the form of voluntary businesses alliance work in a particular market and the old management methods don’t satisfy either the owners or the management any longer. The article reveals the ways of formalization of the collection, generalization, classification, qualification and control processes. The necessity to reform the existing model of business management by improving control functions of the management system was proved in the article. It was mentioned in the article that much more attention is paid to the cost-benefit control but not to the methods of cost formation. The author suggests an individually developed control environment model which takes into account all the peculiarities of enterprise engineering which in turn is based on the principles of targeting, consistency, hierarchy, complexity, continuity, autonomy, apperception, adaptability, etc. The author’s conceptual model includes the setting of goals and objectives that are necessary to solve the task, as well as analysis procedures and operational control models. The article focuses on the control procedures of the proposed conceptual model, which have the opportunities to provide internal users with useful information and to organize feedback on risks monitoring through the integration of control systems with accounting, budgeting and analysis in the process of gathering information for decision making.